Low-Power IoT Node Design for Remote Sensor Networks Using Deep Sleep Protocols - A.Velliangiri (National Journal of Electrical Electronics and Automation Technologies, 2025)
Remote sensor networks working in isolated/infastructure-less environments require ultra-low-power Internet of Things (IoTs) nodes in order to utilize a longeer battery life and limited maintenance. This paper proposes an IoT node architecture design for energy efficient IoT nodes, which utilize the deep-sleep protocol and the adaptive wake-sleep schedule, such that energy consumption is reduced while there is no compromise on the performance of sensing and transmission. The node is equipped with energy efficient micro controllers, optimized firmware for sensing peripheries and a sensor activity based scheduler that activates the node only on requirement. Simulations and prototype tests based on ESP32 and STM32 platforms show that there’s more than 75 percent savings in power consumption in comparison with always on modes. The proposed design is appropriate for environmental verifying, monitoring wildlife and precision agriculture, where power conservation is a major concern.